The Synergistic Effects among Crystal Orientations, Creep Parameters, Local Strain, Macro–Microdeformation, and Polycrystals' Hardness of Boron Alloyed P91 Steels. Issue 9 (11th June 2022) - Akhtar, Modassir; Khajuria, Akhil
Abstract : This article induces proficient microstructure––creep reciprocity by electron backscatter diffraction (EBSD) and impression creep measurements (ICM). The article has further contributed to understanding the synergistic effects of boron in extenuating microstructural degradation. Herein, 22 and 100 ppm boron alloyed P91 steels (P91 and P91B steels, respectively) are subjected to ICM, assessing stress exponent ( n ), threshold stress ( σ Th ), effective activation volume ( V eff ), and activation energy. Base metal and narrowed crept realm of each steel are measured by employing EBSD. ICM results are correlated with crystal orientations and 1) strain accumulation, 2) macroscopic and 3) microscopic deformation resistance, and 4) hardness of grain in polycrystals by calculating kernel average misorientation (KAM), elastic stiffness, grain reference orientation deviation (GROD), and Taylor factor (M) within microstructure before and after ICM. Measurements of P91B steel show a small value of n and V eff and a high value of σ Th and activation energy as regards P91 steel. Lower KAM and stiffness before and after creep, higher GROD in base metal, and lower GROD in the crept realm in P91B steel as regards P91 steel corroborate microstructural homogeneity. M indicates both steels are hard before creep, while ICM moderates hardness. Finally, this study reveals synergistic effects of crystal orientations, KAM, stiffness, GROD, M, and creep. Abstract : This study helps to understand the perplexing nature of boron effects in 9Cr steels through creep and microstructural measurements. These provide an in‐depth understanding of creep–microstructural mechanisms that help to elucidate synergistic effects.